The Effect of Using Differentiated Instructional Strategy on Improving Linguistic Communication Skills of Non-native Students Learning Arabic Language - Alslaiti , Feras (Dirasat: Educational Sciences, 2020)
The purpose of this study was to investigate the effect of using differentiated instructional strategy on improving language communication skills of Arabic language of non-native speakers. To achieve this goal, the researcher prepared two language communication tests (a reading test and a writing test). The reading test consists of (9) multiple choice questions, and the writing test of (9) writing tasks. The sample consisted of (12) male and female non-native students learning Arabic language\ level 4 at Al-Bayt university. A pretest was applied; then students were taught with a differentiated education strategy. After that, the same test was applied. The results of the study showed a statistically significant difference at the level of significance (α=0.05) between the average grades of the two groups on language communication skills due to the teaching strategy variable, for the benefit of the experimental group taught using the differentiated education strategy.